2007
DOI: 10.1007/s00520-006-0211-x
|View full text |Cite
|
Sign up to set email alerts
|

The last 3 days of life in three different care settings in The Netherlands

Abstract: Introduction Little is known about the characteristics of dying in different care settings, such as the hospital, the nursing home, or the home-care setting. Materials and methods We measured the burden of symptoms, medical and nursing interventions, and aspects of communication during the last 3 days of life within each of these settings. We included 239 of 321 patients (74%) who died in one of these settings in the southwest of The Netherlands, between November 2003 and February 2005. After the patient's dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…Interestingly, the scant literature on symptoms in the last days of life focused primarily on the last 48 hours (9, 25, 26) and in other care settings (e.g., hospices, nursing homes) (8, 27, 28). We found that the frequency of many symptoms was high and increased over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the scant literature on symptoms in the last days of life focused primarily on the last 48 hours (9, 25, 26) and in other care settings (e.g., hospices, nursing homes) (8, 27, 28). We found that the frequency of many symptoms was high and increased over time.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, findings from this study are only applicable to cancer patients admitted to APCUs. Because symptom expression may differ by disease and setting (28), further studies are needed to characterize the symptom burden in other populations in the last days of life.…”
Section: Discussionmentioning
confidence: 99%
“…Seven more recent studies showed inconsistencies in what was considered a 'home death', in the measurement of pain and in the groups compared. 50,[54][55][56][57][58][59][60] This highlights the need for greater clarity and consistency in measurement and patient selection.…”
Section: Is Home Care or Home Death Better Than Other Places -For Examentioning
confidence: 99%
“…8,15 Also, previous literature suggests certain characteristics may influence recognition of patients' death in the near future. 16,17 However, related studies have been limited to specific settings, 16,18,19 diagnoses, 16,20,21 age groups, 17,21 and functional states. 17,22 To the best of this study's knowledge, this is the first nationwide study that examines the timing of and the factors associated with recognising death in the near future from a general patient population.…”
Section: Introductionmentioning
confidence: 99%